<span>(7 x 10^−12)(4 x 10^5)
= (7x4) x 10^-7
= 28 x 10^-7
= 2.8 x 10^-6</span>
Answer:
12x -y = -87
Step-by-step explanation:
You can start with the 2-point form of the equation of a line and manipulate it to give you the standard form.
y = (y2 -y1)/(x2 -x1)(x -x1) +y1
y = (-9 -3)/(-8 -(-7))(x -(-7)) +3
y = (-12/-1)(x +7) +3
y = 12x +84 +3
-12x +y = 87 . . . . . subtract the x-term
12x -y = -87 . . . . . . make the leading coefficient positive (per standard form)
9514 1404 393
Answer:
C
Step-by-step explanation:
The step shown indicates that y was eliminated from the equations. For choices A, B, D, this is done by adding the equations together (the y-coefficients are opposites). The result of doing that gives x-terms of 4x, 0x, and 0x, respectively. These x-terms do not match the one given: 2x.
For choice C, the y-term is eliminated by subtracting twice the second equation from the first. Doing that gives ...
(4x +2y) -2(x +y) = (14) -2(3)
4x +2y -2x -2y = 14 -6 . . . . eliminate parentheses
2x = 8 . . . . . . . . . . . . . . collect terms
This would be called an ANGLE.
Hopefully this helps!
21 is greater cause it whole number